Suspension of the National Registry of Evidence-Based Programs and Practices: the importance of adhering to the evidence - Sharon Green-Hennessy (Substance Abuse Treatment, Prevention, and Policy, 2018)
Abstract Recently the United States Assistant Secretary of Mental Health and Substance Use disclosed having suspended the National Registry of Evidence-Based Programs and Practices, stating it was so deficient in both rigor and breadth that it must be replaced. However, a closer examination of her claims about the Registry indicates many of them to be inaccurate. Contrary to her assertions, the Registry is not devoid of medication-assisted treatments for opioid use; nor does it contain but a scant few interventions related to schizophrenia and psychosis. Moreover, many of her criticisms regarding rigor pertain to reviews completed since late 2015, when the Substance Abuse and Mental Health Services Administration altered key aspects of the Registry. In contrast to reviews generated under the 2007 rules, these newer reviews rely on fewer references, incorporate less expert input, are more likely to be based exclusively on gray literature, and are no longer required either to provide dissemination readiness information or meet certain minimum research quality standards. However, only 123 (25.7%) of the 479 Registry interventions have been reviewed solely using the problematic 2015 criteria, with the remaining 356 interventions having a review which use the 2007 guidelines. Yet, rather than address the agency’s recent missteps and expand the Registry’s content coverage, the agency appears to have decided to invest considerable resources into replacing it, relying heavily on expert consensus versus empirical data in its initial attempt to do so. This raises questions about the agency’s current commitment to evidence-based practice.